CHARACTER VALUES OF IMPLEMENTATION REYOG EXTRACURRICULAR EDUCATION AT SDN 2 TONATAN, PONOROGO REGENCY - Fitri, Dhesanty; Yanuartuti, Setyo (Solah, 2026)
Reyog Extracurricular Activities are one of the extracurricular activities at SDN 2 Tonatan, Ponorogo Regency, which serve as a forum and shelter for students to appreciate and channel their talents in the fields of dance and music. Reyog extracurricular activities provide learning about students' skills in dancing, in addition to having an impact on students related to character values. The purpose of this study is to analyze character values ​​in the implementation of extracurricular activities and the impact of the implementation of Reyog Extracurricular for students of SDN 2 Tonatan, Ponorogo Regency. To solve problems about character values, researchers use Sofyan's character value theory. Then the concept of learning impact uses Sudirman's theory. The research method uses a qualitative descriptive method with data collection using observation techniques, interviews, document studies, and literature studies. Analysis through the stages of data reduction, data presentation, and data validation. The results of the study show that the implementation of Reyog extracurricular activities is carried out routinely at SDN 2 Tonatan. The materials taught are Jathil, Warok, Bujangganong, Klono Sewandono and Singo Barong dances. The material is taught by trainers using demonstration methods. The character values ​​of the Reyog extracurricular activity are found in the learning materials and the learning process. These impacts include the instructional effect related to students' knowledge and skills. Meanwhile, the nurturing effect relates to the character values ​​that emerge in the personalities of students who participate in the Reyog extracurricular activity at SDN 2 Tonatan. The character values ​​of the Reyog extracurricular activity at SDN 2 Tonatan include discipline, hard work, responsibility, self-confidence, cooperation, tolerance, and courtesy. Keywords:Implementation of Reyog extracurricular activities, character values, impact